2022
DOI: 10.5435/jaaosglobal-d-21-00139
|View full text |Cite
|
Sign up to set email alerts
|

Academic, Leadership, and Demographic Characteristics of Orthopaedic Sports Medicine Division Chiefs in the United States

Abstract: Introduction: Division chiefs (DCs) play an integral role within the department, making critical decisions and helping shape the future of both the division and the department. This study aimed to investigate the demographic characteristics and scholarly work of DCs in academic orthopaedic sports medicine division in the United States. Methods: Orthopaedic residency programs at academic centers were identified using the Association of American Medical Colleges' Electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Maqsoodi et al. published a study on the division chiefs of Orthopaedic Sports Medicine, from 191 programs identified, 96% were male and 86% were Caucasian, which is similar to this current study [20] .…”
Section: Discussionsupporting
confidence: 88%
“…Maqsoodi et al. published a study on the division chiefs of Orthopaedic Sports Medicine, from 191 programs identified, 96% were male and 86% were Caucasian, which is similar to this current study [20] .…”
Section: Discussionsupporting
confidence: 88%
“…At the level of chair, vice chair, program director, assistant program director, and division chief (DC), females occupied 0 (0%), 2 (50%), 6 (40%), 2 (40%), and 3 (4.7%) positions, respectively. Maqsoodi et al 16 used the Fellowship and Residency Electronic Interactive Database residency program database as of 2020 to identify academic orthopedic surgery programs and noted the gender, race, and ethnicity of the 100 DC. DCs were predominantly male at 96% (n = 96) vs. female at 4% (n = 4), and 86% (n = 86) were White, whereas 2% (n = 2) were URMs, with 1 African American and 1 Hispanic/Latino (Table V).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have investigated diversity within orthopedic leadership 14-16 , academic rank, and research productivity 17-20 . However, no study currently exists that synthesizes these data for orthopedic sports medicine at large and compares data across these metrics of engagement within orthopedic sports medicine.…”
mentioning
confidence: 99%
“…L ack of diversity among orthopaedic surgeons is a persistent problem. Many studies have documented disparities based on characteristics such as race and sex, affecting orthopaedic applicants, residents, practicing surgeons, and leaders in the field [16][17][18] . The "leaky pipeline" metaphor posits how increasing attrition, failure to progress, or choosing alternate courses results in fewer women at each stage of career advancement [19][20][21] .…”
Section: Discussionmentioning
confidence: 99%